Proteomic analysis of outer membrane vesicles derived from the type A5 Strain of Mannheimia haemolytica - Shang, Ke; Gao, Yuanji; Du, Jiangbo; Liu, Chang; Dai, Jinglei; Zhang, Junfeng; Jia, Yanyan; Yu, Zuhua; Chen, Songbiao; Liu, Zhongyu (Frontiers in Cellular and Infection Microbiology, 2025)
Mannheimia haemolytica (M. haemolytica) cause mastitis in sheep, acute sepsis in newborn lambs, and co-infections with various pathogens, leading to bovine respiratory disease syndrome (BRDS), these infections have resulted in significant economic losses to both domestic and international farming industries. An in-depth understanding of the pathogenic mechanisms of M. haemolytica is crucial for the prevention and control of this disease. Outer membrane vesicles (OMVs) play a vital role in bacterial pathogenesis, serving as key mediators of interactions between Gram-negative bacteria and their hosts. However, the specific role of OMVs in the pathogenic process of M. haemolytica remains poorly understood. To address this, we isolated OMVs from the Mannheimia haemolytica Type A5 strain (MH-5) using ultracentrifugation and subsequently characterized their secretory properties, protein composition, and immunogenicity through electron microscopy, liquid chromatography-tandem mass spectrometry (LC-MS/MS), and cellular experiments. The electron microscopy results indicated that the MH-5 strain secreted OMVs under natural growth conditions. Proteomic and bioinformatics analyses revealed that these OMVs contained 282 proteins, with significant enrichment in proteins related to immunity, iron metabolism, and catalytic activity. Cellular experiments demonstrated that, compared to the control group, the OMVs group exhibited a significant increase in the mRNA expression of IL-1β, IL-6, and TNF-α, with secretion levels increasing in a dose-dependent manner, thereby enhancing the inflammatory response. These findings lay the groundwork for further exploration of the role of OMVs in the pathogenesis of M. haemolytica and provide insights for the development of effective vaccines and antibiotics against this pathogen.